EVIDENCE-BASED POLICY IN THE FORMULATION OF LOCAL REGULATIONS: A CASE STUDY OF THE RIAU PROVINCE HOUSING AND SETTLEMENT DEVELOPMENT PLAN POLICY - Hadi , Ahmad; Bedasari, Hafzana; Safitri, Syofiatul; Notatema, Ben Hansel; Putra, Indra Mardeni (Journal of Social Politics and Governance (JSPG), 2025)
Housing and settlement issues in Riau Province continue to increase in line with population growth, urbanization, high housing backlog rates, and the existence of slums and disaster-prone areas. This study aims to examine the application of EBP in the Riau Province RP3KP through three main aspects: the commitment of policy actors, the use of data and scientific knowledge, and the organizational readiness for implementation. The study uses a post-positivist qualitative approach with data collection techniques in the form of in-depth interviews and documentation studies. The analysis was conducted using the interactive model of Miles, Huberman, and Saldana. The results show that political support for the RP3KP is relatively strong, but the involvement of non-governmental actors is still limited. Scientifically, the drafting of the RP3KP has utilized primary and secondary data, but the integration of local empirical findings is still weak. From an implementation perspective, institutional capacity and cross-sector coordination are not yet fully ready, especially in relation to synchronization with the Spatial Plan (RTRW). These findings emphasize the need to strengthen EBP so that the RP3KP is more adaptive, contextual, and effective in addressing the complexity of housing issues in Riau.